Horner–Wadsworth–Emmons Reactions in THF: Effect of Hydroperoxide Species - Jarvis, Amanda G.; Wells, Elizabeth R.; Fairlamb, Ian J. S. (Synlett, 2013)
Horner–Wadsworth–Emmons (HWE) reactions routinely employ tetrahydrofuran (THF) as the reaction solvent. In this paper we show that THF adducts (derived from THF–hydroperoxide species) of HWE phosphonate ester compounds are formed under microwave irradiation (i.e., under pressure), or in the presence of a reductant [e.g., P(OEt)3] in a conventionally heated reaction.
Keywords: alkenes; phosphorus; peroxides; furan; reduction